Caregiver-involved reminiscence for persons with dementia: a scoping review protocol - Xin Min Lim; Esther Yin Hui Chew; George Glass Frederick; Ee-Yuee Chan (Systematic Reviews)
Abstract Background Reminiscence has been shown to improve cognitive functions in persons with dementia and maintain meaningful relationships with their familial caregivers. However, there is a dearth of reviews on caregiver-involved or caregiver-led reminiscence activities. Objectives This protocol aims to outline the process for a scoping review of the existing literature on caregiver-involved reminiscence for persons with dementia. Inclusion criteria This review will examine studies involving persons with dementia diagnosed with any form of dementia (i.e. Alzheimer’s, vascular dementia, Lewy body, or frontotemporal dementia) and their familial caregivers. It will focus on reminiscence activities involving any recalling and storytelling of past events, sometimes known as “life story work”, where caregivers may actively or passively participate or facilitate. The context is community care, specifically in a home setting. The review will cover literature including primary research, reviews, meta-analyses, and case reports. Methods Literature written in English will be searched in major relevant databases which are MEDLINE, Embase, CINAHL and PsycINFO, Cochrane, and Web of Science. Based on the inclusion criteria, the scoping review will include reviews, quantitative primary studies, qualitative primary studies, and mixed-methods studies. Two reviewers will independently select the articles based on the agreed search strategy and inclusion criteria. Data will be extracted by the two reviewers independently using a standardised data extraction tool. Descriptive mapping and descriptive content analysis will be used to analyse and present the results. Discussion This protocol will outline the scoping review of current literature on caregiver-involved reminiscence for persons with dementia. The scoping review’s findings aim to identify the research gaps in this emerging field where reminiscence is not just pertaining to persons with dementia but involved or even led by caregivers. This will thereby provide guidance for future studies on caregiver engagement with persons with dementia in the community and outpatient settings and provide insights into effective caregiver-involved reminiscence activities. Practical challenges include study heterogeneity on specific caregiver involvement. Systematic review registration https://doi.org/10.17605/OSF.IO/H2ZST .